Training as A Growth Strategy for Trade SMEs in The Veracruz-Boca Del Río Conurbated Area - Roque Uscanga-Martínez; José G. Vargas-Hernández (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research shows, based on the statistics, that the main entities that generate employment are small and medium-sized enterprises; the survey of the National Institute of Statistics and Geography (INEGI) serves as sustenance added to those generated by the National Micro-business Survey (ENAMIN ). In the context of training, the results of this study reflect that training for workers is not a priority. Consequently, they do not have it, even though it is regulated as a worker's right by the Ley Federal del Trabajo and an obligation for the business sector. The result shows the companies' conformity with the duality of the benefit of training since this fundamental part that could allow them to achieve greater competitiveness in the market is not found in their planning.